2020
DOI: 10.1038/s41598-020-66794-0
|View full text |Cite
|
Sign up to set email alerts
|

Effects of magnetic monopoles charge on the cracking reversal processes in artificial square ices

Abstract: In this paper we perform nanofabrication of square artificial spin ices with different lattice parameters, in order to investigate the roles of vertex excitation on the features of the system. In particular, the character of magnetic charge distribution asymmetry on the vertices are observed under magnetic hysteresis loop experiments. We then compare our results with simulation using an emergent Hamiltonian containing objects such as magnetic monopoles and dipoles in the vertices of the array (instead of the u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 33 publications
3
12
0
Order By: Relevance
“…percentile of monopoles being generated in a sharp shape curve for lowest magnetic field. Those phenomena promoted by aluminum layer are qualitatively similar to what was observed in samples with different lattice parameters 37 where it was found that increasing distances among nanomagnets at the vertex reduces the stray field from the nanomagnets, affecting directly the magnetic monopole and dipole intensity. The present aluminum layer effect suggest fascinating interaction among metallic electron gas with emergent magnetic monopole and dipole, decreasing its intensity in a sort of electric screening.…”
Section: Resultssupporting
confidence: 78%
See 4 more Smart Citations
“…percentile of monopoles being generated in a sharp shape curve for lowest magnetic field. Those phenomena promoted by aluminum layer are qualitatively similar to what was observed in samples with different lattice parameters 37 where it was found that increasing distances among nanomagnets at the vertex reduces the stray field from the nanomagnets, affecting directly the magnetic monopole and dipole intensity. The present aluminum layer effect suggest fascinating interaction among metallic electron gas with emergent magnetic monopole and dipole, decreasing its intensity in a sort of electric screening.…”
Section: Resultssupporting
confidence: 78%
“…To the best of our knowledge, experimental investigations or calculations of proximity effects by noble metals in nanostructures were not reported so far and in this work we are going to use an emergent excitation model 34 to investigate how the magnetization interface decrease in nanomagnets due to charge carrier excess would imply in the observed behavior of magnetization and monopole density in the reversal processes of an ASI. In our previous work 34,37 , numerical solution of a model of emergent excitations that considers the presence of magnetic monopoles of charge q and magnetic dipoles of moment | M| on the vertices, presented a qualitative match with the evolution of magnetization and monopole density in reversal process of experimental square ASI arrays 37 . In this model 34 , the total magnetic field at nanoisland i, B tot i , is the sum of the field produced by the excitations on the vertices (see Refs.…”
Section: Resultsmentioning
confidence: 81%
See 3 more Smart Citations